Glutathione redox potential in the mitochondrial intermembrane space is linked to the cytosol and impacts the Mia40 redox state - Kojer, Kerstin; Bien, Melanie; Dick, Tobias P. (The EMBO journal, 2012)
Glutathione is an important mediator and regulator of cellular redox processes. Detailed knowledge of local glutathione redox potential (EGSH) dynamics is critical to understand the network of redox processes and their influence on cellular function. Using dynamic oxidant recovery assays together with EGSH‐specific fluorescent reporters, we investigate the glutathione pools of the cytosol, mitochondrial matrix and intermembrane space (IMS). We demonstrate that the glutathione pools of IMS and cytosol are dynamically interconnected via porins. In contrast, no appreciable communication was observed between the glutathione pools of the IMS and matrix. By modulating redox pathways in the cytosol and IMS, we find that the cytosolic glutathione reductase system is the major determinant of EGSH in the IMS, thus explaining a steady‐state EGSH in the IMS which is similar to the cytosol. Moreover, we show that the local EGSH contributes to the partially reduced redox state of the IMS oxidoreductase Mia40 in vivo. Taken together, we provide a comprehensive mechanistic picture of the IMS redox milieu and define the redox influences on Mia40 in living cells.
Gesehen am 22.11.2018